Treatment of Natural Rubber Wastewater using Photoactive Nanocomposite Membrane PSf/sulfonated ZnO: Performance Evaluation, HAZOP, and Risk Analysis - Tutuk Djoko Kusworo; Widayat Widayat; Hadiyanto Hadiyanto (Diponegoro University, 2022)
The application of nanocomposite membranes for high organic wastewater treatment faces several problems such as impurities and low permeate flux. In this study, sulfonated ZnO nanoparticles were incorporated in the PSf membrane. SEM images reveal that sZnO has good compatibility with PSf polymers and the FTIR spectrum also forms sulfonic acid groups on the composite membrane. The addition of sZnO into PSf increased the PWF value but overloading caused a significant decrease. The surface hydrophilicity of the membrane was also enhanced by the incorporation of sZnO into the PSf membrane. The performance evaluation showed a significant increase in flux from 9.0 to 14.5 L.m-2.h-1 and a disappointment rate for ammonium ion (NH4+) up to 87%. Increased hydrophilicity was also revealed by decreasing the air contact angle from 79.33° to 55.67°. PVA-coated membranes can increase COD rejection up to 88%, which is 8 times higher than uncoated composite membranes. The PVA coating also reduced the tendency of organic fouling on the membrane during rubber wastewater filtration by reducing the total fouling resistance from 14.2 x 10-11 to 9.91 x 10-11 m-1. The HAZOP and risk analysis were also studied in this work regarding on their practical application in industrial scale..